Students’ Creativity For Writing About Environment By Using Storybird Website - Sujiatmoko, Ahmad Heki; Shelley Salsabila Nanda Puspita (CV. Kalimasada Group Profesional, 2024)
One of the aspects needed to get success in writing is creativity. This study was aimed at investigating students’ perception towards creativity by using the Storybird website as a digital platform in writing skill. The study employed a descriptive quantitative within a survey design. The instrument of the research used a questionnaire. The subjects of the research 60 students at one of the universities in Malang - Indonesia. The results showed that the students positively thought about the importance of creativity in supporting writing skills by using the Storybird application. In this case, they felt to be flexible in creating new ideas, to be original in finding new ideas, and to be curious in imagining what they could write about environment as the crucial topic. Finally, the creativity built for writing through using the Storybird application also impacted to the increase of the vocabulary acquisition, writing performance, and organization of their writing. Hence, it is also recommended that EFL teachers should lead the students build their creativities in writing by using the Storybird application.